Legal Regulation of Electronic Payment of Funds Under Iraqi Law - صباح, محمد فواز (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The electronic payment system is a new generation of payment methods for money, which is based on communication technology and the Internet on the one hand, and smart systems associated with banks and specialized money companies on the other hand, through which anyone in the world can transfer money or make purchases from his place of residence at any time Standard, simple effort, low cost and safe way. The urgent need for this system has emerged with the emergence of electronic commerce, and today this idea is developing to enter wide and important areas, starting with paying salaries and periodic bills, passing through buying from traditional and electronic stores, and ending with the emergence of the digital electronic wallet. The need is now increasing and urgent in view of the increase and diversity of financial transactions, so it was necessary to go along with this new system that allows everyone to pay his dues and cover his needs electronically anywhere and anytime without the need to carry traditional money. In view of the many advantages that this system gives, most legislation has been regulating it by law, including the electronic payment which issued the Electronic Payment Service System Law No. (3) of 2014.